Gifford Lectures: over 100 years of renowned lectures on natural theology - Gifford Lectures staff, author (Colorado State University. Libraries, 1997)
The Gifford Lectures web site providing the Lectures' history, overview, sponsoring universities, news and other related information; also including an online database to search books derived from the Lectures, lecture summaries, and lecturers' biographies.
Keywords: Gifford Lectureships; lecturers; Gifford Lectures